2018
DOI: 10.18549/pharmpract.2018.03.1351
|View full text |Cite
|
Sign up to set email alerts
|

Resource-based theory of competitive advantage – a framework for pharmacy practice innovation research

Abstract: A growing body of research demonstrates the effectiveness of evidence-based pharmacy practice, but too many practice innovations fail to survive past the initial implementation and study phase. This paper presents the resource-based theory of competitive advantage as a framework for describing, understanding, and predicting the adoption and dissemination pharmacy service innovations into routine practice. The theory argues that the sustainability of any business innovation (e.g., pharmacy service) is based upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
(57 reference statements)
1
24
0
1
Order By: Relevance
“…Jabir et al (2019) identified the competitive advantage as the unique status of the organization that enables it to cope rivals, while Khan et al (2019) indicated that competitive advantage fundamentally derived from the organization's resources and capabilities. The resources have been referred to the assets an organization acquired that deem as a stash of obtainable factors and one of an organization's strengths and weaknesses (Bowman & Ambrosini, 2003;Holdford, 2018). The capabilities are considered as the organization ability to integrate its resources together for developing its products by managing brand which is based on the organization knowledge about its market needs (Holdford, 2018;Maja et al, 2018;Takahashi & Sander, 2017).…”
Section: Sustainable Competitive Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…Jabir et al (2019) identified the competitive advantage as the unique status of the organization that enables it to cope rivals, while Khan et al (2019) indicated that competitive advantage fundamentally derived from the organization's resources and capabilities. The resources have been referred to the assets an organization acquired that deem as a stash of obtainable factors and one of an organization's strengths and weaknesses (Bowman & Ambrosini, 2003;Holdford, 2018). The capabilities are considered as the organization ability to integrate its resources together for developing its products by managing brand which is based on the organization knowledge about its market needs (Holdford, 2018;Maja et al, 2018;Takahashi & Sander, 2017).…”
Section: Sustainable Competitive Advantagementioning
confidence: 99%
“…The resources have been referred to the assets an organization acquired that deem as a stash of obtainable factors and one of an organization's strengths and weaknesses (Bowman & Ambrosini, 2003;Holdford, 2018). The capabilities are considered as the organization ability to integrate its resources together for developing its products by managing brand which is based on the organization knowledge about its market needs (Holdford, 2018;Maja et al, 2018;Takahashi & Sander, 2017). The term sustainable competitive advantage has received immense importance since Porter (1980) drawn the broad lines of how organizations developed their strategies to interact with their markets through the generic competitive strategies classified into cost leadership, differentiation, or focus (Quaye & Mensah, 2019).…”
Section: Sustainable Competitive Advantagementioning
confidence: 99%
“…A clearly written blueprint can be used in implementation science to allow comparisons at a glance of the exact nature of service innovations in comparison to the status quo. They are also helpful in describing the competitive advantage of one innovation over another, allowing pharmacists to develop service offerings that are sustainable over time [11].…”
Section: Uses Of Service Blueprintsmentioning
confidence: 99%
“…3,4 It is vital to understanding and studying the competitive advantage of pharmacists and realizing the value provided for customers and stakeholders. 5 Currently, there is confusion in the literature about basic concepts associated with pharmacists interventions. 6 Constructs lack common definitions, taxonomies, and frameworks.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 It is vital to understanding and studying the competitive advantage of pharmacists and realizing the value provided for customers and stakeholders. 5 …”
Section: Introductionmentioning
confidence: 99%